Diastematomyelia: A Case with Familial Aggregation of Neural Tube Defects. (2004) - Kanbur, Nuray Öksüz; Güner, Pınar; Derman, Orhan; Akalan, Nejat; Cila, Ayşenur; Kutluk, Tezer
Abstract : Intrauterine neural tube defects, meningomyelocele, and diastematomyelia are developmental errors at different stages of the closure of the neural tube. The familial aggregation of these neural tube defects is not previously reported in the literature and should make one think about a common embryogenesis and a possible common mechanism of etiopathogenesis leading to anomalies at different stages of this embryogenesis. This paper presents a 12-year-old Turkish boy with diastematomyelia who was suspected with a demonstrative dermatologic finding without any neurologic sign and diagnosed with magnetic resonance imaging (MRI). He has a positive family history of a stillbirth with neural tube defect, an exitus with meningomyelocele, and an epileptic child in his female siblings.